Identification of Coagulation and Fibrinolysis-Associated Biomarkers With Implications for Preeclampsia - Yujie Liu; Tingting Chen; Cuifang Fan (Genetics Research)
Conclusion: Our bioinformatic analysis resulted in a diagnostic model (CYP19A1, C1QBP, GHR, and PSMA3) for PE related to coagulation and fibrinolysis. We also conducted immune microenvironment and drug sensitivity analyses, providing insights into PE diagnosis and treatment.